1987
DOI: 10.1177/000331978703800402
|View full text |Cite
|
Sign up to set email alerts
|

Systolic Hypertension in Patients with Arteriosclerosis Obliterans of the Lower Limbs

Abstract: Intraarterial blood pressure, brachial artery compliance and diameter, and pulse wave velocity were determined in 20 patients with arteriosclerosis obliterans of the lower limbs (AOD) in comparison with 10 age- and sex-matched controls. With the same mean arterial pressure as in controls, patients with AOD exhibited a significant increase in systolic pressure and decrease in diastolic pressure, resulting in an increase in pulse pressure. While brachial artery diameter and pulse wave velocity remained nearly wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 15 publications
3
8
0
Order By: Relevance
“…Although the opposite was the reality, the present results were consistent with previous findings by Simonson et al (14) and Eliakim et al (15) showing that PWV levels in the heart-feet and the femoral-dorsal segments were reduced in PAD. In contrast, Safar et al (13) reported that brachial-radial PWV in patients with PAD was within the normal range. Taken together, patients with lower-limb PAD do not necessarily have changes in PWV of arteries in the upper extremities, whereas they have reduced PWV in the leg arteries.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although the opposite was the reality, the present results were consistent with previous findings by Simonson et al (14) and Eliakim et al (15) showing that PWV levels in the heart-feet and the femoral-dorsal segments were reduced in PAD. In contrast, Safar et al (13) reported that brachial-radial PWV in patients with PAD was within the normal range. Taken together, patients with lower-limb PAD do not necessarily have changes in PWV of arteries in the upper extremities, whereas they have reduced PWV in the leg arteries.…”
Section: Discussionmentioning
confidence: 90%
“…In an early study by Haynes (12), no significant difference was observed in PWV of the aorta, carotid-brachial, or femoral-dorsalis segments between subjects with and without PAD. Safar et al (13) measured brachial-radial PWV in 20 patients with PAD, and found that it remained within the normal range. In contrast, Simonson et al (14) and Eliakim et al (15) reported that heart-feet PWV, and femoral-dorsalis PWV were reduced in patients with PAD, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In most subjects with PAD, ejection fraction and ventricular ejection are preserved, giving no cardiac explanation to the frequency of systolic hypertension in this population. 10,11 Increased SBP in subjects with PAD is mainly because of increased arterial stiffness and disturbed timing and amplitude of central wave reflections. [12][13][14] More specifically, reflection sites are closer from the heart than in normal subjects, because of the importance of structural alterations of the aortic bifurcations, as extensively shown from arteriography.…”
Section: Discussionmentioning
confidence: 99%
“…18 Guidelines such as the sixth report of the joint National Committee on the Prevention, Declaration, Evaluation and Treatment of High Blood Pressure include peripheral arterial disease as a marker of …”
Section: Hypertensionmentioning
confidence: 99%